Efficacy of nasal irrigation and oral rinse with sodium bicarbonate solution on virus clearance for COVID-19 patients - Wang, Tairong; Zhang, Yue; Zhang, Rong; Mao, Ye; Yan, Junhai; Long, Yiwen; Chen, Qiaofeng; Li, Xiaojing; Wang, Huixiang; Huang, Shuai; Zhu, Chao; Teng, Bin; et al. (Frontiers in Public Health, 2023)
Background Recent studies have shown that the infectivity of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is reduced under alkaline conditions. The purpose of this study is to assess the effect of nasal irrigation and oral rinse with sodium bicarbonate solution on virus clearance among COVID-19 patients. Materials and methods COVID-19 patients were recruited and randomly divided into two group, i.e., the experimental group and the control group. The experimental group received regular care plus nasal irrigation and oral rinse with 5% sodium bicarbonate solution, while the control group only received regular care. Nasopharyngeal and oropharyngeal swab samples were collected daily for reverse transcription-polymerase chain reaction (RT-PCR) assays. The negative conversion time and hospitalization time of the patients were recorded, and the results were statistically analyzed. Results A total of 55 COVID-19 patients with mild or moderate symptoms were included in our study. There was no significant difference in gender, age and health status between the two groups. The average negative conversion time was 1.63 days after treatment with sodium bicarbonate, and the average hospitalization time of the control group and the experimental group were 12.53 and 7.7 days, respectively. Conclusions Nasal irrigation and oral rinse with 5% sodium bicarbonate solution is effective in virus clearance for COVID-19 patients.